“I am this one walking beside me”: Laing’s Theory of Ontological Insecurity in Faulkner’s Light in August - Ivana Pehar ([sic])
This paper offers an analysis of two characters, Joe Christmas and Joanna Burden, in William Faulkner’s Light in August. The characters are analyzed through R.D. Laing’s concept of ontological insecurity. In the search for the roots of ontological insecurity, special attention is given to the childhood years of these characters, and to the race-related trauma originating in that period. The aim is to show that both these characters exhibit schizoid personality traits as a consequence of that trauma, and also as a result of the society they live in. Namely, Joe and Joanna never work through their initial trauma because it is actually reinforced by their society.Key words: William Faulkner, Light in August, R. D. Laing, ontological insecurityAn articulate critic of the South, Lillian Smith in her Killers of the Dream presents southern culture as a rigid society that controls its citizens through ruthless socialization. Drawing primarily from her own experience, she describes southern culture as “dissonant,” demanding that southerners simultaneously embrace contradictory ideas without seeing them as contradictory: